Prospective Ultrasound Screening of Men With Cerebrovascular Disease for Abdominal Aortic Aneurysms. (September 2021) - Vänni, Ville; Turtiainen, Johanna; Kaustio, Ulla; Toivanen, Jari; Rusanen, Minna; Hernesniemi, Jussi
Background: The prevalence of abdominal aortic aneurysms is higher in population with other vascular comorbidities, especially among men. Utility of screening among patients with cerebrovascular disease is unclear. Objective: To determine the prevalence of abdominal aortic aneurysm in male patients with diagnosed cerebrovascular disease manifested by transient ischemic attack or stroke. Methods: Between May 2013 and May 2014, all consecutive male patients undergoing carotid ultrasound in single tertiary center with a catchment area of 179, 000 inhabitants were evaluated for ultrasound screening of abdominal aortic aneurysm. Abdominal aortic aneurysm was defined as maximum diameter of infrarenal aorta 30 mm or more. Results: Of 105 (n = 105) consecutively evaluated male patients, only 69% (n = 72) were eligible for the study and underwent aortic screening. Reason for ineligibility was most often poor general medical condition (n = 29). Mean age of screened patients was 66 years (SD 9.8 years). Half of the screened patients suffered stroke (n = 36). The incidence of abdominal aortic aneurysm was 5.6% (n = 4). All found abdominal aortic aneurysms were small and did not require immediate surgical intervention. During a follow-up period of over 4 years, none of the aneurysms exhibited tendency for growth. Conclusions: The male population with cerebrovascular disease is comorbid and frail. Only, moderate prevalence of abdominal aortic aneurysms can be found in this subpopulation.